Analysis of Land Dispute Resolution in Court : A Case Study at LDP LAW FIRM & PARTNERS - Jeffenri Lumban Batu; July Esther (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The resolution of land disputes through the judicial process is a step taken when non-litigation settlement efforts fail. This process involves a series of legal procedures aimed at enforcing land rights, including proof of ownership and other related rights. This article aims to analyze the procedures, challenges, and effectiveness of land dispute resolution in court. Using a normative-empirical approach, this study finds that although the judicial system provides a clear mechanism, there are several obstacles, such as lengthy legal processes, high costs, and the complexity of proving ownership, which can delay dispute resolution. In this regard, it is important for the parties involved to understand the applicable legal procedures and utilize alternative dispute resolution methods that can expedite land dispute resolution, such as mediation and arbitration. This study also recommends improvements in the judicial system and more efficient approaches to handling land disputes in the future.